STRATEGY FOR STRENGTHENING THE PERSONAL COMPETENCIES OF ISLAMIC RELIGIOUS EDUCATION LECTURERS AT STATE GENERAL UNIVERSITIES IN MAKASSAR CITY - Musbaing; Abdul Azis Muslimin; Syahrikal; Abrina Maulidnawati Jumrah; Alamsyah Halim (Academic Bright Collaboration, 2026)
This study aims to describe the personality competencies possessed by Islamic Religious Education lecturers at state public universities in Makassar City and to identify strategies for implementing and strengthening these competencies in higher education contexts. This study employed a qualitative field research design. Data were collected through observation, interviews, and documentation. The analysis used a personality competence performance approach to examine how Islamic Religious Education lecturers demonstrate, apply, and develop their personality competencies in academic and social settings. The findings show that Islamic Religious Education lecturers at state public universities in Makassar City contribute to the creation of an academic environment that supports students’ intellectual growth and character formation holistically. Their personality competencies are reflected in the integration of religious values into daily academic practices, active involvement in student development, cooperation and collaboration within inclusive academic environments, participation in curriculum development, and the demonstration of wise and prudent leadership. These competencies not only influence students’ personal and academic development but also provide broader positive contributions to universities and society. This study implies that the development of personality competencies among Islamic Religious Education lecturers at public universities in Makassar needs to be strengthened through patterns that are relevant to the needs of Islamic Religious Education in public higher education. Personality competencies should also be adjusted to the scientific expertise of each lecturer so that the knowledge, attitudes, and values delivered remain consistent with the academic discipline of Islamic Religious Education. This study is limited to the description of personality competencies and strengthening strategies among Islamic Religious Education lecturers at state public universities in Makassar City. This study provides an overview of personality competencies and strengthening strategies among Islamic Religious Education lecturers at three state public universities in Makassar City: Universitas Hasanuddin, Universitas Negeri Makassar, and Politeknik Negeri Ujungpandang.